Preliminary study of osteoporosis and osteopenia among postmenopausal women in mukim Tasek, Daerah Badang from November 2006 to November 2007 - Emil Fazliq, Mohd (2008)
This is a prospective cross sectional descriptive study with aims to identify the prevalence of Osteoporosis and Osteopenia in early postmenopausal women in Mukim Tasek, Daerah Badang. Systematic sampling of the population in Mukim Tasek, Kota Bharu was conducted from June 2007 to November 2007. A total of 54 women post menopause age 45-65 years old, who are disease free and with intact uterus were recruited. Mean menopausal age at 50.56 ± 2.93 years. Prevalence of osteoporosis is 14% and osteopenia 30%. The weight, height and primary education have positive correlation with bone mineral density (BMD) where low body weight, shorter height and primary education have increase risk of osteopenia and. No correlation noted between age, age at menopause, duration of menses or parity with BMD. Smoking and exercise has no association with BMD. The result of the study comparable to urban midlife population of Malaysia. With high prevalence of osteopenia and osteoporosis in the population, the problem of fracture will be major health issues to the society and nation.